Nurturing creativity in comfort; Gently pushing the boundaries within a zone of safety - Carlota Torrents; Sílvia Garcías de Ves; Matthew Bourke; Veronique Richard (PLoS ONE, 2026)
In today’s rapidly evolving world, fostering creativity within educational settings is essential to prepare individuals for complex global challenges. This study explores the dynamic interplay between individuals and their environments in nurturing creative potential. The research focuses on the influence of participants’ experiences of challenge, comfort, destabilization, support, connection, engagement, and emotions on developing students’ creative potential throughout a creative dance intervention. Ninety-three university students (62 men and 35 women; Mean age: 20.5) participated in 36 creative dance classes over four months. Creative self-efficacy, tolerance for ambiguity, emotional creativity, and ideational behaviors were assessed before and after the intervention. After every class, a brief questionnaire assessing students’ experience of creative dance was filled out. A two-step approach, firstly estimating a mixed effect location scale model and secondly following a simpler linear regression model, was applied to assess how variations in the students’ experience of the creative dance program impact creativity-related variables. Contrary to the common belief that discomfort and stepping out of one’s comfort zone are necessary for creative growth, the findings suggest a more nuanced relationship. While challenges and destabilizing activities can stimulate creativity by preventing routine responses, the study found that comfort, support, and positive emotional experiences were significantly associated with creative self-efficacy and emotional creativity. Social support and connection emerged as critical factors in nurturing creativity. Environments characterized by psychological safety, where individuals feel secure to take risks without fear of negative consequences, seemed to be associated with creative engagement. The formation of group synergies through shared goals and mutual trust were associated with innovative outcomes and individual creative development. The study also highlighted the importance of consistent engagement and positive emotional experiences in fostering tolerance for ambiguity and ideational behaviors. While consistent support and engagement were linked to a greater ability to tolerate ambiguity, variability in peer connection and emotional responses during collaborative processes seemed to be associated with creative ideation. In conclusion, the research emphasizes the significance of person-environment interactions in creative development interventions. Supportive and comfortable environments that foster positive connections and emotional well-being were more consistently associated with favourable creativity-related outcomes than environments centred primarily on challenge. Integrating creativity and emotional awareness into educational practices, particularly in movement-based activities like dance and physical education, can unlock the full potential of these disciplines and better prepare individuals for the complexities of the modern world.